2006
DOI: 10.1021/ja063632f
|View full text |Cite
|
Sign up to set email alerts
|

A Catalytic Nanomaterial-Based Optical Chemo-Sensor Array

Abstract: An optical sensor array based on chemiluminescent images from spots of nanomaterials has been employed to recognize odorous samples. The distinctive images obtained from the array permit identification of a wide range of analytes, even homologous compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 148 publications
(118 citation statements)
references
References 20 publications
6
110
0
2
Order By: Relevance
“…These materials are potentially suitable for processing as a chip-mounted sensor array. Na et al found that luminescent efficiencies of the CTL are different for a compound on different nanomaterials [28]. As shown in Fig.…”
Section: Catalytic Nanomaterial-based Optical Chemosensor Array For Rmentioning
confidence: 95%
“…These materials are potentially suitable for processing as a chip-mounted sensor array. Na et al found that luminescent efficiencies of the CTL are different for a compound on different nanomaterials [28]. As shown in Fig.…”
Section: Catalytic Nanomaterial-based Optical Chemosensor Array For Rmentioning
confidence: 95%
“…Zhang and coworkers proposed nanosized TiO 2 as the sensing material to detect ethanol and acetone [82], which was considered as a pioneering work for the combination of nanomaterials and CTL-based chemosensors. Since then, CTL-based chemosensors with the adoption of various nanocatalysts have been intensively researched by many academic groups such as Zhang's [83][84][85][86] [96][97][98][99][100][101] and so on. Due to the high chemical stability, specific structure and composition as well as the catalytic, electronic and optical properties, g-C 3 N 4 can provide greater versatility in carrying out gas adsorption, selective catalytic and sensing processes; therefore, g-C 3 N 4 -based materials may provide new opportunities to develop new CTL-sensing materials.…”
Section: Cataluminescencementioning
confidence: 99%
“…CTL 传感器阵列广泛 应用于物质鉴别和区分. 张新荣等 [15] 基于分析物在不 同的纳米材料阵列表面的发光强度不同, 综合各个发光 强度组成指纹图谱来对分析物进行区分: 设计了识别三 甲胺、硫化氢和乙醇的 CTL 传感器阵列; 另外, 他们将 发光强度指纹图谱结合线性鉴别分析模型, 设计了可以 区分香烟中芳香气体的 CTL 传感器阵列, 成功识别 6 种 不同品牌的香烟 [16] . 那娜等 [17] 通过对烃类物质进行等 离子体激活, 以增强烃类物质的 CTL 响应信号, 利用 3 行 4 列组成的 CTL 传感器阵列快速识别烃类物质, 成功 区分了癌症病人和健康人群的呼出气体.…”
Section: 引言unclassified